Flavor anomalies, the diphoton excess and a dark matter candidate - Bauer, Martin; Neubert, Matthias (Arxiv, 2016)
We argue that the diphoton excess recently reported by ATLAS and CMS can be explained, along with several anomalies seen in the flavor sector, in models where a Standard-Model singlet scalar resonance with mass